USING MEDIA BRAKING SYSTEM STAND USE TO IMPROVE STUDENT LEARNING OUTCOMES OF D3 AUTOMOTIVE DPTM FPTK UPI - Nursalam, Muhamad; Mubarak, Ibnu; Sulaeman, Sulaeman; Permana, Tatang (Journal of Mechanical Engineering Education, 2020)
The purpose of this study was to determineehow1much difference in studenttlearning outcomes before and after the use of the media braking system stand in the teaching and learning process of Diploma 3 Automotive DPTM FPTK UPI students on the competence of the Disc Brake System. The research method used is an experiment with pre-experiment design, and the2research design uses one-groups0pretest-posttest designi. The sample in this studyswas automotive Diploma 3 students who contracted automotive chassis courses totaling 12 1people. The iinstrument used in this study is a written test that has been tested by expert judgment. The results showed the average pretest value was 39.50; posttest 83.20; and Normalization-Gain value of 0.72 included in the high7category, in this study also tested the research hypothesis with associativetype, where the result is the correlation value obtained of 0.708 and a coefficient of determination of 50.1%. This study shows that the use of media braking system stand influences the increase in learning outcomes (scores) on the competence of disc brake systems.